2011
DOI: 10.1097/wnn.0b013e3182239308
|View full text |Cite
|
Sign up to set email alerts
|

Higher Autonomic Activation Predicts Better Performance in Iowa Gambling Task

Abstract: The results are compatible with the idea that a higher basal activation of autonomic nervous system is beneficial for subsequent decision-making process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 32 publications
3
25
0
Order By: Relevance
“…This performance is comparable to that of adult samples investigated in previous studies (Bayard et al, 2011;Brand et al, 2009;Drucaroff et al, 2011;Schiebener et al, 2011). The variable "number of decisions for one single number" was skewed (skewness = 2.17).…”
Section: Hypothesis 1: Main Effect Of Age On Decision Making Under Risupporting
confidence: 80%
“…This performance is comparable to that of adult samples investigated in previous studies (Bayard et al, 2011;Brand et al, 2009;Drucaroff et al, 2011;Schiebener et al, 2011). The variable "number of decisions for one single number" was skewed (skewness = 2.17).…”
Section: Hypothesis 1: Main Effect Of Age On Decision Making Under Risupporting
confidence: 80%
“…that a higher basal activation of the autonomic nervous system is benefi cial for subsequent decision-making processes ( 6 ). In turn, due to the fact that autonomic activity plays a key role in adapting to a changing environment, crewmembers may benefi t from training to regulate their autonomic and central nervous system responses.…”
Section: Discussionmentioning
confidence: 99%
“…As it has a relatively rapid influence on cardiac activity, one common method of estimating PNS function is via the high-frequency spectral component of HRV (HF-HRV; Berntson et al, 1997). Other studies have interpreted the low-frequency component of HRV (LF-HRV) as a reflection of sympathetic cardiac influence (Drucaroff et al, 2011; Dulleck et al, 2014), although this interpretation has been critisized (Reyes del Paso et al, 2013; see Discussion). The neurovisceral integration model also delineates neuroanatomical evidence for the relationship between cardiac signals and cognitive function.…”
Section: Introductionmentioning
confidence: 95%
“…Transient heart rate, however, has been shown to slow directly after a loss in a gambling task, and this decrease in heart rate begins earlier (often prior to the outcome) in individuals who have better general performance in the task (Crone et al, 2004). It has also been shown that individuals with a higher power in the low frequency component of resting HRV generally perform better on gambling tasks (Drucaroff et al, 2011), and there is some evidence that direct vagus stimulation (which increases HRV) can enhance performance in these tasks (Martin et al, 2004). Furthermore, HRV (and its high frequency component) decreases during “stressful” unfair economic offers (such as those in the ultimatum game; Armin et al, 2011; Dulleck et al, 2014).…”
Section: Introductionmentioning
confidence: 99%